Background Characteristics and Cognitive Factors as Determinants of Oral Health in Pregnant Women, Tehran, Iran: A Cross-Sectional Study - Mina Shirmohammadi; Simin Zahra Mohebbi; Samane Razeghi; Mohammad Reza Khami; Ahmad Reza Shamshiri; Hoda Bahramian (Frontiers in Dentistry, 2024)
Objectives: Pregnancy can lead to oral health issues, yet many women remain unaware of the potential negative impact on their pregnancy. This study aimed to assess the dental and periodontal health of pregnant women in Tehran, Iran, and identify its associated factors.